Economic development and environmental degradation: A panel ARDL/PMG model for EU-27 countries - Ionut Jianu (Journal of Financial Studies, 2022)
This research aims to examine the relationship between economic development and environmental degradation in European Union over the period 2000-2019 using a Panel ARDL/PMG model. In this respect, I have used GDP per capita expressed in PPS to catch the economic development and greenhouse gas emission per capita as a proxy for environmental degradation. The study confirms a positive impact of greenhouse gas emissions (per capita) on GDP (per capita) on short-run, but also a negative effect on long-run - the long-run effect being present in 24 EU Member States.
Keywords: C33; Q53; O11; Q56; 330; economic development; environment; greenhouse gas emissions; GDP; Panel ARDL / PMG model